2003
DOI: 10.1007/s10255-003-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Nonparametric Least-squares Test for Checking a Polynomial Relationship

Abstract: Recently, Gijbels and Rousson [6] suggested a new approach, called nonparametric least-squares test, to check polynomial regression relationships. Although this test procedure is not only simple but also powerful in most cases, there are several other parameters to be chosen in addition to the kernel and bandwidth. As shown in their paper, choice of these parameters is crucial but sometimes intractable. We propose in this paper a new statistic which is based on sample variance of the locally estimated pth deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The coefficients a, b and the degrees of freedom r are chosen in such a way that the first three moments of a + bχ 2 r are made to match those of the quadratic form. Both some theoretical examination [3] and extensive simulations [5,16,18] have demonstrated that the three-moment χ 2 approximation performs quite well in many situations. In our case, by neglecting the biases of the estimation and with the similar derivations in [18], we obtain…”
Section: Three-moment χ 2 Approximationmentioning
confidence: 96%
See 1 more Smart Citation
“…The coefficients a, b and the degrees of freedom r are chosen in such a way that the first three moments of a + bχ 2 r are made to match those of the quadratic form. Both some theoretical examination [3] and extensive simulations [5,16,18] have demonstrated that the three-moment χ 2 approximation performs quite well in many situations. In our case, by neglecting the biases of the estimation and with the similar derivations in [18], we obtain…”
Section: Three-moment χ 2 Approximationmentioning
confidence: 96%
“…Therefore, the proposed test statistic is a ratio of quadratic forms in normal variables and the pvalue in (16) can also be transformed as the probability of a quadratic form of normal variables being greater than zero (for example, see [1,18]). Therefore, many algorithms and routines exist for computing the p-value of the test including the exact method [16] and many approximate methods (for example, see [1] for a review).…”
Section: Null Distribution Of the Test Statisticmentioning
confidence: 99%
“…& Gijbels i. (1996) made more detailed description for the local linear estimation [3][4][5][6] . In addition to the long-term trend, the variable quantities with short-range changes are important studied in earth science.…”
Section: Local Polynomialmentioning
confidence: 99%
“…For the details of the three-moment w 2 approximation, refer to Azzalini and Bowman (1993) and Leung et al (2000b). In particular, see Mei et al (2003) for dealing with the case of tr(Q 3 i ) 0 (i 1, 2).…”
Section: Final Remarksmentioning
confidence: 99%
“…(The reasonableness of the assumptions will be explained in remark 2). With these assumptions and under the null hypotheses H 0 , the p-value in equation ( 18) can be computed by using the three-moment w 2 approximation of the quadratic forms in normal variables (eg see Azzalini and Bowman, 1993;Leung et al, 2000b;Mei et al, 2003). Here, we give only the final computational formula.…”
mentioning
confidence: 99%